Controlling the Dissolution of Realgar by Neutron Activation - Pujić, Z.; Zovko, E. (Kemija u Industriji, 2009)
Radioanalytical method for monitoring of separation of arsenic from realgar ore through As-76 was described. The procedure follows the distribution of radioactive components between a liquid and a solid phase in any kind of chemical treatment.The method is applicable in examination of metallurgical procedures with natural materials that are characterized with a high cross section for neutron capture. The method can be applied in examination of samples containing mercury (II) sulphide HgS, which are not suitable for conventional chemical treatments concerning ecological risks.The samples examined were from Vareš mine zone - a sample of realgar ore and a sample of dolomite. The realgar seam has not been treated separately, but the sample has been collected by flotation in a concentrate which is a mixture of different ores in Vares mine area. We assumed that such seams should be treated separately, and not as a part of an ore concentrate, because arsenic is only a trace element in a concentrate collected (0.2 % – 0.4 %), and its separation is therefore difficult. A sample of realgar ore has been irradiated with a neutron source americium – 241/beryllium with neutron flux 2.6×107 n s-1. The radio analytical procedure proposed consists of three main phases:– The investigated sample is irradiated in a neutron source and gamma-spectrometrically charecterised.– An identical sample is exposed to any kind of chemical treatment. A part of the sample that isnot dissolved is then separated and the remainder is gamma-spectrometrically characterized aswell.– When the obtained gamma spectra are compared, the information on distribution of radionuclides is gained, and the yield of dissolving process is defined.Reliability of the neutron activation method depends on the neutron source used, but also on the quality of gamma-spectrometer. A typical gamma spectrum of a realgar sample (0.5 g), after it has been irradiated in a neutron source, was recorded on a 200-channel NaI crystal spectrometer (Fig. 1). Possible interferences come from Sb-122, Sb-124 and Zn-69 m, concerning the energies used in the spectrochemical measurement (they could not be separated from As-76). In order to check the reliability of the method of radiochemical marking in following the dissolving of realgar,we have conducted additional gamma-spectrochemical measurements of an irradiated realgar sample, using a semi-conducting 1000 channel Ge/Li spectrometer (Fig. 2). The two gammaspectra show that all As-76 energies are present (558 keV, 657 keV and 1215 keV (Fig. 1 and Fig. 2).The conclusion is that a processing of numerical data from energy spectra and the main energy level (0.56 MeV for As-76) can be used for following of dissolving of realgar on a scintillation spectrometer as well, because there are no measurable interferences from other elements in the energy level zone observed. In the main energy zone for As-76, the half-life recorded is 25.4, and the literature value is 26.5 hrs, and the error of ± 5 % is acceptable.This confirms the above written conclusion.